The effect of natural Gongura roselle fiber on the mechanical properties of 3D printed ABS and PLA composites - Appusamy, Anandha Moorthy; Nanjappan, Natarajan; Eswaran, Prakash; Subramanian, Madheswaran (Polimery, 2022)
The influence of the natural Gongura roselle fiber on the tensile and flexural properties as well as on Shore D hardness of acrylonitrile-butadiene-styrene (ABS) and poly (lactic acid) (PLA) was investigated. The composites were printed in fused deposition modeling (FDM) 3D technique. The addition of natural fiber improved the mechanical properties of the tested composites, while the flexural strength, modulus and hardness were better in the case of ABS-based composite. Whereas, PLA-based composites showed higher tensile strength. The influence of the nozzle angle on the mechanical properties of the composites was also investigated. The best results have been obtained when using an angle of 0 °.